Failure Analysis of Road Embankment - Pawan Mahindrakar, Arif khan, Kaushik shelke, Prathyush Kummangoden, Sayed Anwar (International Journal of Advanced Science and Technology, 2020)
The risk of failure of transportation embankments due to seepage induced by temporary and occasional impoundment staking place on the upstream side as a consequence of exceptional rainfalls is frequently underestimated. Based on the case study of a road embankment in Nilje – Taloja collapsed in 2019 due to an upstream impoundment that occurred after few hours of a very intense rainfall. A proposed analytical method consisting of seepage, stress-deformation, and stability analyses is performed. The modelling technique proposed not only facilitates the computation of factor of safety but also the deformation.Keywords: Embankment, Flash flood, Stability, Finite element method